Safety and efficacy of a feed additive consisting of Lactiplantibacillus plantarum DSM 34271 as a silage additive for all animal species (Lactosan GmbH & Co.KG) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on Lactiplantibacillus plantarum DSM 34271 when used as a technological additive to improve ensiling of fresh plant material. The additive is intended for use in easy and moderately difficult to ensile fresh plant material for all animal species at a proposed minimum concentration of 1 × 108 colony forming units (CFU)/kg fresh plant material. The bacterial species L. plantarum is considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. The identity of the strain was established and no acquired antimicrobial resistance genes of concern were detected. Therefore, the FEEDAP Panel concluded that the use of the strain as a silage additive is considered safe for all the animal species, for consumers of products from animals fed the treated silage and for the environment. Regarding user safety, the additive containing Lactiplantibacillus plantarum DSM 34271 should be considered as a potential skin and respiratory sensitiser, and any exposure through skin and respiratory tract is considered a risk. One preparation was shown not to be irritant to skin or eyes. However, the Panel cannot assess the irritation potential of other possible preparations. The FEEDAP Panel concluded that Lactiplantibacillus plantarum DSM 34271 has the potential to improve the fermentation of the silage prepared from fresh plant material with a DM range of 30%–35% at a minimum concentration of 1 × 108 CFU/kg fresh material.